Comparison of solvent-dehydrated allograft dermis and autograft rectus fascia for pubovaginal sling: questionnaire-based analysis - Onur, Rahmi; Singla, Ajay; Kobashi, Kathleen C. (Springer, 2008)
Objectives To evaluate the efficacy of pubovaginal sling using human cadaveric dermis processed by solvent dehydration and compare results to those of another group in which autograft rectus fascia was used. Material and methods The efficacy of autologous rectus fascia (group 1, n = 25) or solvent-dehydrated cadaveric dermis (group 2, n = 24) for pubovaginal sling were compared in women with stress urinary incontinence (SUI). Surgical outcome, patient satisfaction and quality of life was assessed by the urogenital distress inventory (UDI-6) and the incontinence impact questionnaire (IIQ-7). Results Mean follow-up for patients in group 1 and group 2 were 18 and 13 months, respectively. Our questionnaire-based assessment revealed that SUI was either cured or improved in a total of 21 (84%) patients in group 1 and 19 (79%) patients in group 2. No statistically significant difference was found for the overall success (P < 0.05) and no major complications were encountered in both groups. Conclusions Use of allograft dermis as an alternative to autologous rectus fascia for pubovaginal sling had comparable improvement in patient satisfaction and quality of life at intermediate term.
Keywords: urinary incontinence; allograft; dermis; autologous; quality of life